Effects of dietary nitrate supplementation on isometric performance and physiological responses in college bodybuilders: a randomized, double-blind, crossover study - Wang, Lijun; Zhao, Ruohan; Yan, Yuhang; Zhang, Hongli; Yan, Ruixin; Zhu, Yifan; Han, Zhuohong; Qu, Yue; Wang, Ruonan; Li, Yicheng; Chao, Ruolin (Frontiers in Nutrition, 2025)
IntroductionIn bodybuilding competitions, athletes are required to hold static poses for extended periods. This study aimed to evaluate the effects of acute beetroot juice (BJ) supplementation on isometric muscle endurance in college bodybuilding athletes.MethodsSixteen male college bodybuilding athletes participated in a randomized, double-blind, crossover study conducted over three weeks with four laboratory visits. The first visit involved explaining the experimental protocol and performing the maximal voluntary isometric contraction (MVIC) test. The second visit familiarized participants with the testing procedures. During subsequent visits, participants consumed either BJ (250 ml,∼ 12.48 mmol of NO3−) or PL (250 ml,∼ 0.0005 mmol of NO3−), and blood samples were collected before testing to measure nitrate (NO3−) and nitrite (NO2−) concentrations. Participants then performed three rounds of isometric circuit endurance tests (ICET), during which heart rate (HR), ratings of perceived exertion (RPE), and blood lactate levels were recorded. Each round of ICET consisted of four subtests targeting the elbow flexors, core muscles, forearm muscles, and knee extensors, maintaining 70% of MVIC until fatigue. Additionally, surface electromyography (sEMG) was used to record and analyze muscle activity.ResultsCompared to PL, acute BJ supplementation resulted in a 10.87-fold and 1.57-fold increase in serum NO3− and NO2− levels, respectively (P < 0.001). No significant differences were observed in MVIC peak torque under different conditions (P > 0.05). In the third round of testing (ICET-3), endurance improved by 14.9, 25.4, and 25.2% for the elbow flexors, forearm muscles, and knee extensors, respectively. No significant differences in root mean square (RMS) values were observed between the BJ and PL groups (P > 0.05).DiscussionThese data suggest that acute beetroot juice supplementation had no significant effect on MVIC in college bodybuilding athletes but improved endurance in certain muscle groups during ICET. This suggests that nitrates may enhance endurance by optimizing intermittent recovery processes rather than directly increasing strength.